The effects of mandatory IAS/IFRS adoption: the perception of SMEs listed in Italy - Capalbo, Francesco; Smarra, Margherita; Sorrentino, Marco (Piccola Impresa / Small Business, 2019)
With effect from 2005, EU Regulation 1606/2002 made compliance with IFRS mandatory for the consolidated accounts of companies with securities traded on a regulated market of the EU member States. Immediately after that, it is possible to observe in literature innumerable empirical research on the effects of mandatory IFRS adoption in the EU. Generally, the studies focused on the opinion of big publicly-traded companies or small privately held businesses, mostly unlisted. Within this stream, the aim of this paper is instead to investigate the perception that SMEs listed at Alternative Indipendent Market of Italian Stock Exchange have about the possible effects of IFRS adoption. The results of the online survey are in line both with the prevailing literature and with the empirical investigations carried out up to now, as the opinion of SMEs with securities traded in Italy about the use of IFRS is generally negative.